2016
DOI: 10.1007/s12583-015-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon U-Pb geochronology and Lu-Hf isotopic compositions of the Wuliangshan metasediment rocks in SW Yunnan (China) and its provenance implications

Abstract: The Wuliangshan Group occurs to the east of the Lancang giant igneous zone in SW Yunnan, and is mainly composed of low-grade metamorphosed sedimentary rocks. The group has been considered as the syn-orogenic product of the Baoshan with Simao-Indochina blocks. However, its depositional time and provenance remain to be poorly constrained. This paper presents zircon U-Pb dating and Lu-Hf-isotopic data for five representative sandstone samples from the Wuliangshan Group. The detrital grains yield a major age-peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
6
9
0
Order By: Relevance
“…As a result, our age-data, along with the reported results in SW Yunnan and SE Asia portions of the Sibumasu (e.g., Chen et al, 2007;Dong et al, 2013aDong et al, , 2013bKawakami et al, 2014;S. Liu et al, 2009;Lin et al, 2013;Quek et al, 2018;Song et al, 2007;Wang et al, 2011Wang et al, , 2012X. Xing et al, 2016;Zhao et al, 2016), reveal the presence of a zone of latest Cambrian to early Silurian igneous rocks, which extends from SW Yunnan (China) to South Thailand, then to western Peninsular Malaysia, and on to East Sumatra.…”
Section: Formation Time Of the Early Paleozoic Granitoids Of The Sibumasusupporting
confidence: 77%
See 3 more Smart Citations
“…As a result, our age-data, along with the reported results in SW Yunnan and SE Asia portions of the Sibumasu (e.g., Chen et al, 2007;Dong et al, 2013aDong et al, , 2013bKawakami et al, 2014;S. Liu et al, 2009;Lin et al, 2013;Quek et al, 2018;Song et al, 2007;Wang et al, 2011Wang et al, , 2012X. Xing et al, 2016;Zhao et al, 2016), reveal the presence of a zone of latest Cambrian to early Silurian igneous rocks, which extends from SW Yunnan (China) to South Thailand, then to western Peninsular Malaysia, and on to East Sumatra.…”
Section: Formation Time Of the Early Paleozoic Granitoids Of The Sibumasusupporting
confidence: 77%
“…Our dating results show the orthogneiss and migmatite (11ML-68C 1 and -77A) from the Pake Complex (traditionally mapped as part of the Pake Formation) formed at 474-462 Ma (Figures 5a and 5b). Such data, along with published age data (e.g., Xing et al, 2016), suggest that the previously defined Precambrian Ximeng Group is most likely a metamorphic complex involving orthogneiss, migmitite, granite, and volcano-sedimentary rocks formed in the latest Cambrian-Ordovician in age (Figure 10b).…”
Section: Latest Cambrian-ordovician Ximeng Complexsupporting
confidence: 69%
See 2 more Smart Citations
“…Previous studies have suggested that outcrops in the Ximeng area are composed of Precambrian metamorphic basement, which consists of the Proterozoic Laojiezi Formation granulite (Pt 3 l ), Pake Formation schist (Pt 3 p ) and Early Paleozoic Wangya Formation schist (Pz 1 w ) (Yunnan Geology and Mineral Resources Development Bureau, 1982). In recent years, zircon U–Pb dating has provided new chronological information about magmatic events in the Ximeng area, showing that the Early Paleozoic gneissic granites are present in the Laojiezi and Pake formations with emplacement ages ranging from 430.37 to 465.50 Ma (Chen et al, 2017; Wang et al, 2013; Xing et al, 2015). These ages correspond with commonly observed Early Paleozoic granite magmatism in the Tengchong and Baoshan blocks, which are considered to be related to the Proto‐Tethyan Andean orogenesis (Chen et al, 2017; Dong et al, 2010; Li et al, 2010, 2012; Liu et al, 2009; Wang et al, 2013; Xing et al, 2015); however, Early Paleozoic granite magmatism‐related mineralization has not yet been reported in the Ximeng area.…”
Section: Discussionmentioning
confidence: 99%